2020
DOI: 10.3389/fpls.2019.01674
|View full text |Cite
|
Sign up to set email alerts
|

Transient Expression of Dengue Virus NS1 Antigen in Nicotiana benthamiana for Use as a Diagnostic Antigen

Abstract: Dengue is a viral disease that represents a significant threat to global public health since billions of people are now at risk of infection by this mosquito-borne virus. The implementation of extensive screening tests is indispensable to control this disease, and the Dengue virus non-structural protein 1 (NS1) is a promising antigen for the serological diagnosis of dengue fever. Plant-based systems can be a safe and costeffective alternative for the production of dengue virus antigens. In this work, two strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…These same vectors were used to the expression of monoclonal antibodies and reached a yield between 1.2 and 1.4 g/kg. Recently, Marques et al (2020) demonstrated the transient expression of the dengue virus NS1 protein in N. benthamiana for diagnostic purposes. Using an elastin-like polypeptide (ELP) as a fusion tag, the authors obtained 445 mg/kg yield, more than double that obtained in this work, but less than other works that used the transient expression approach.…”
Section: Discussionmentioning
confidence: 99%
“…These same vectors were used to the expression of monoclonal antibodies and reached a yield between 1.2 and 1.4 g/kg. Recently, Marques et al (2020) demonstrated the transient expression of the dengue virus NS1 protein in N. benthamiana for diagnostic purposes. Using an elastin-like polypeptide (ELP) as a fusion tag, the authors obtained 445 mg/kg yield, more than double that obtained in this work, but less than other works that used the transient expression approach.…”
Section: Discussionmentioning
confidence: 99%
“…The NS1 protein from DENV-2 was expressed in tobacco as a diagnostic reagent for ELISA tests because it has a greater sensitivity than DENV-1 with only a slightly lower specificity (Amaro et al, 2015;Marques et al, 2019;). The first dengue VLP vaccines were produced based on DENV-3 polyprotein in lettuce chloroplasts (Kanagaraj et al, 2011) and cross-reacted with the anti-dengue primary polyclonal antibody.…”
Section: Dengue Fevermentioning
confidence: 99%
“…As is the case for other endemic diseases that affect primarily developing countries, plants offer a promising platform for vaccine and antibody production because of the low costs, ease of distribution and the particular efficacy of VLP candidates. Recombinant proteins based on consensus envelope protein domain III (cEDIII) and non‐structural protein 1 (NS1) have been produced by transient expression in N. benthamiana (Kim et al ., 2018 ; Marques et al ., 2019 ; Pang et al ., 2019 ) and in transgenic tobacco (Amaro et al ., 2015 ; Gottschamel et al ., 2016 ; Kim et al ., 2010 , 2015 , 2017b ;), lettuce (van Eerde et al ., 2019 ; Kanagaraj et al ., 2011 ; Maldaner et al ., 2013 ), rice (Kim et al ., 2013 , 2014 , 2016 ) and potato (Kim et al ., 2017a ). Transient expression produces soluble antigens with maximum yields of 600 mg/kg fresh leaf biomass (Martinez et al ., 2010 ) although an HBcAg‐cEDIII fusion protein was mostly insoluble and the soluble fraction was not detected by Western blot (Pang et al ., 2019 ).…”
Section: Molecular Farming As a Strategy To Address Endemic Diseasesmentioning
confidence: 99%
“…Plant-derived antigens have demonstrable utility in the serological detection of a number of infectious diseases, such as the Dengue virus [ 44 , 45 ], West Nile Virus [ 46 ], Rift Valley fever virus [ 47 ], and Hepatitis E virus [ 15 ]. These studies demonstrate that plants are among the most rapid, prolific, and flexible producers of diagnostic immunogenic reagents.…”
Section: Introductionmentioning
confidence: 99%